Allolobophora caliginosa as bioindicator for chitosan–saponin–bentonite nanocomposite contaminated soil - Ghada Mohamed Ahmed; Nesma A. Mostafa; Manal El-Garhy; Sohair R. Fahmy; Ayman Saber Mohamed; Sara Bayoumi Ali (Scientific Reports)
Abstract The usage of nanocomposites in water treatment has risen, resulting in their leaking into the soil, which is a major environmental concern. Earthworm (Allolobophora caliginosa) is used as a bioindicator that can accumulate most pollutants, even if they are present in low concentrations. The present study aimed to use earthworms as biological indicator for chitosan–saponin–bentonite nanocomposite (CSB NCs) in the soil. Earthworms were exposed to CSB NCs (0, 0.025, 0.05, 0.1, and 0.15 mg/500 g soil) for 7 consecutive days. CSB NCs induced significant damage and instability of the lysosomal membranes in coelomocytes in a dose-dependent manner. The exposure to CSB NCs resulted in a notable change in earthworm biochemical levels. Light microscopy revealed histological damage in the body wall and intestine of earthworm exposed to CSB NC. In addition, scanning electron microscopy showed morphological alterations in the anterior, dorsal, and ventral parts of the earthworm as well as in the anal region because of exposure to CSB NC. The present study demonstrated that earthworms exposed to CSB NCs had a depletion in antioxidants and presented histological alterations especially in high doses of nanocomposite. Also, treated earthworms showed substantial alterations in the surface topography. Exposure to CSB NC caused physiological and histological alteration in earthworms. This study emphasizes the urgent need to evaluate the environmental safety of nanocomposites used in water treatment.